A review on the Huoqiu banded iron formation (BIF), southeast margin of the North China Craton: Genesis of iron deposits and implications for exploration - Yang, Xiaoyong; Liu, Lei; Lee, Insung; Wang, Bohua; Du, Zhenbao; Wang, Qicai; Wang, Yuxian; Sun, Weidong (Ore geology reviews, 2014)
The Huoqiu iron ore field in northwest Anhui Province is located in the North China Craton (NCC). As a large banded iron formation (BIF) iron ore field, ore bodies occur in a middle-high grade of Neoarchean metamorphic formation, forming a banded silicon–iron series from north to south. The main ore bodies can be divided into two sub-belts from bottom to upper layers, i.e. the A+B ore belt consisting of leptynite–schist–magnetite–quartz formation, and the D ore belt consisting of schist–marble–hematite–quartz formation. Based on a dataset from geological settings, geophysical and geochemical exploration, ore-forming conditions and structural analysis of the iron deposit, we discuss structural types, sedimentary environments, deep tectonic and ore-controlling factors as well as characteristics and distribution of this colossal BIF ore field in the Huoqiu region. Using LA-ICP-MS techniques, we obtained the oldest U–Pb age of ca. 2.7Ga for plagioclase amphibolite as its original rock, and 1.8Ga for magmatic granite in the Huoqiu Group. The Hf isotopes of zircon were also determined, resulting in the oldest Hf model age of 3.5Ga. Geochemical data indicate that the protolithes of amphibolites belong to a series of subalkaline rocks with enrichments of large ion lithophile elements and depletions of high field strength elements, which are typical volcanic arc rocks. The amphibolites have low K2O concentrations with low ratios of Ti/V (22.7 to 25.9 averaging 24.5), similar to island arc tholeiite. This suggests that the iron deposit and BIF are of the Superior type in the Huoqiu region. [Display omitted] •Amphibolite protolith belongs to a series of subalkaline rock, and BIF occurrences formed in back-arc basin.•Stable isotopes indicate interaction of mantle-derived fluid with the sedimentary rocks by long–time metasomatism.•The iron ore deposit in the Huoqiu region is regarded as a Superior type.